1988
DOI: 10.1148/radiology.168.1.3132731
|View full text |Cite
|
Sign up to set email alerts
|

Association of heterotopic gray matter with seizures: MR imaging. Work in progress.

Abstract: Heterotopic gray matter, which previously had been associated with severe congenital malformations of the brain and developmental delay, was found without these associated conditions. The authors found ten cases of heterotopic gray matter on magnetic resonance (MR) images. The lesions had a signal intensity that was isointense compared with that of gray matter on T1, spin-density, and T2-weighted images. Nine of the ten cases were associated with a seizure disorder. The tenth case, discovered during a workup f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Human malformations are normally identified in vivo during neuroimaging (66)(67)(68), or after neuropathologic analysis of resected tissue ( I 1,69,70), or after death by histologic analysis (7 1). Although there is a strong association between malformations and epilepsy, it is possible to have a cortical malformation in the absence of an epileptic phenotype.…”
Section: From Epilepsy To Malformation: Clinical Featuresmentioning
confidence: 99%
“…Human malformations are normally identified in vivo during neuroimaging (66)(67)(68), or after neuropathologic analysis of resected tissue ( I 1,69,70), or after death by histologic analysis (7 1). Although there is a strong association between malformations and epilepsy, it is possible to have a cortical malformation in the absence of an epileptic phenotype.…”
Section: From Epilepsy To Malformation: Clinical Featuresmentioning
confidence: 99%
“…ously described PNH cases (5,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)21) (Table 3), which also suggests a different etiology for bilateral and unilateral PNH. The clear female predominance (86%, including the present cases), the frequent familial occurrence of symmetrically diffuse cases (13)(14)(15)(16)(17)19), and the positive family history for epilepsy (19, present study), all suggest that genetic factors may play a role in determining the brain malformation in at least some bilaterally affected patients.…”
Section: Classification and Possible Origin Of Pnhmentioning
confidence: 99%
“…In the last 10 years, a number of reports have been published concerning patients affected by periventricular nodular heterotopia (PNH), diagnosed by computed to-mography (CT) (7) or magnetic resonance imaging (MRI) (5,(8)(9)(10)(11)(12). These studies have stressed the predominance of females, the possible occurrence in members of the same family (13)(14)(15)(16)(17), the absence of any major neurological or mental deficits, and the frequent incidence of epilepsy.…”
mentioning
confidence: 99%
“…Several studies have shown a consistently unfavourable neurological outcome of band heterotopias (Smith et al 1988, Barkovich and Kjos 1992, Huttenlocher et al 1994. Bilateral periventricular nodular heterotopia, on the other hand, generally has a more favourable outcome (Dobyns et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral whitematter heterotopias can be focal, bilateral (diffuse) nodular, or diffuse laminar (band heterotopias) in distribution (Barkovich et al 1989). Seizures are present in all three types of heterotopias (Smith et al 1988, Barkovich and Kjos 1992, Huttenlocher et al 1994. These children frequently have abnormalities of motor function and cognitive development, particularly those with band heterotopias who have had the most consistently unfavourable neurological outcome (Barkovich and Kjos 1992).…”
Section: *Correspondence To Author At Above Addressmentioning
confidence: 99%